The Relationship Between Understanding the Nature of Science and Teaching Methods Among Biology Teachers in Tabuk City - Dr. Nuha Mustafa Al-Obaidan (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This study aimed to identify the relationship between the right understanding of the nature of science and teaching methods used by biology teachers in Tabuk city. The researcher used the descriptive method to achieve the study objectives. The data was collected by using the questionnaire as a tool for collecting the study sample's data. This questionnaire contained 25 items and included the basic axis to be studied. The validity of the tool was confirmed by several tests and criteria and by using statistical methods such as (T-tests), repetitions, and percentage. The results showed that there is a big relationship between science nature and teaching methods. The level of scores for choosing teaching methods among biology teachers in the city of Tabuk is high, and that there are no statistically significant differences at the significance level of 0.05 or less in the attitudes of the study sample members regarding choosing teaching methods according to the variable of years of experience of the teacher. The level of understanding of the nature of science among female biology teachers in the city of Tabuk is high. This axis included eleven statements. It was found that there are ten of the statements related to the level of understanding of the nature of science among female biology teachers in the city of Tabuk that came with a degree of yes, and there is one statement related to the level of understanding of the nature of science among biology teachers in the city of Tabuk was "sometimes". According to these results, the study suggests some recommendations: It is necessary for curriculum designers to pay attention to including and emphasizing the nature of science in the curricula, to training teachers during the period of practical education on science practices, and to organizing training courses to help teachers on scientific practices in teaching.